Um sistema de geração automática de roteiros de audiodescrição - Campos, Virginia Pinto (2015)
Audio description (AD) is a fundamental accessibility feature for blind or low vision people. However, this feature is not used widely due to the high cost and time involved in its development. This paper presents a solution for automatic generation of audio description, called CineAD. The solution detects gaps in speech and generates these descriptions from the analysis of the original script and subtitles. Alternatively, the solution can be incorporated into a speech synthesis tool or used by a professional. To evaluate the solution, we developed a set of experiments with blind users and audio description specialists. The results show that the proposed solution is able to generate descriptions of the most important events of the film, reducing the barriers of blind people to access cinema.